2018
DOI: 10.1186/s12885-018-5107-x
|View full text |Cite
|
Sign up to set email alerts
|

Projected lifetime cancer risks from occupational radiation exposure among diagnostic medical radiation workers in South Korea

Abstract: BackgroundTimely assessment of cancer risk from current radiation exposure among medical radiation workers can contribute to the development of strategies to prevent excessive occupational radiation exposure. The purpose of the present study is to estimate the lifetime risk of cancers induced by occupational radiation exposure among medical radiation workers.MethodsUsing estimated organ doses and the RadRAT risk assessment tool, the lifetime cancer risk was estimated among medical radiation workers who were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Carcinogenic risks following radiation exposure have been revealed to increase with age and enhance the risk of cell inflammation and the loss of oxidant/antioxidant equilibrium ( 47 , 48 ). Age is one of the risk factors that has been associated with breast cancer in women, particularly those exposed to radiation ( 49 ). The results of the present study are in accordance with those of a previous study, which reported that radiologic technologists of an older age who worked in an environment with radiation exhibited a higher lifetime attributable risk of breast cancer compared with that in other occupational groups, including radiologists, dentists and nurses ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenic risks following radiation exposure have been revealed to increase with age and enhance the risk of cell inflammation and the loss of oxidant/antioxidant equilibrium ( 47 , 48 ). Age is one of the risk factors that has been associated with breast cancer in women, particularly those exposed to radiation ( 49 ). The results of the present study are in accordance with those of a previous study, which reported that radiologic technologists of an older age who worked in an environment with radiation exhibited a higher lifetime attributable risk of breast cancer compared with that in other occupational groups, including radiologists, dentists and nurses ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historical radiation dose reconstruction was performed and organ-specific radiation doses were estimated for the cohort. 6 The findings of overall mortality, 7 thyroid cancer incidence, 8 circulatory disease morbidity, 9 suicide death 10 and projected lifetime cancer risks 11 were reported for this cohort. We have extended this study by linking the latest data on cancer incidence to investigate the role of occupational radiation exposure in cancer development among diagnostic medical radiation workers.…”
Section: Workplacementioning
confidence: 77%
“…In addition, an epidemiological study on the cancer risk due to chronic occupational exposure to low-dose radiation among medical radiation workers, doctors, and dentists have shown a significant increase in the prevalence of solid cancers and leukemia. 22 The occupational risk from low-dose radiation has been studied using dosimetry data collected from radiation workers and their medical records. However, dosimetry data from diagnostic medical imaging procedures performed for patients cannot be obtained directly to determine the effects of radiation exposure on health.…”
Section: Discussionmentioning
confidence: 99%